LEXICAL COMPETENCE AND THE USE OF DICTIONARIES IN AN APROACH TO THE TEACHING OF PORTUGUESE AS A HOST LANGUAGE - Fernandes, Alan Tocantins (2019)
The aim of this article is to discuss, through a theoretical reflection, the potential of a more complete lexical approach and the use of dictionaries in the teaching of Portuguese as a Host Language (PLA), with a focus on the Brazilian context, given the importance of the learning of Portuguese in the process of integration and interaction for people seeking refuge in Brazil. With the arrival of immigrants and refugees, new theoretical and practical knowledge is necessary for teaching PLA and must be articulated with other approaches, taking into account the needs of learners. It is concluded that lexicographic works can be potential collaborating tools for the learner of foreign language and of great importance to understand and to appropriate the way the language is organized, as well as to contributing in the continuous development of the language and for the culture of the host country. In addition, the approach can also contribute to the emancipatory character so desired in PLA teaching and the empowerment of minority groups.